(untitled) (Islamic Sciences Journal, 2025)
ABSTRACT This research aims to understand the true concept of opposition among the scholars of the principles of jurisprudence (usul al-fiqh), by clarifying its meaning and related aspects, and examining the scholars’ opinions on it through their quotations. Research methodology: Inductive-deductive. Among the most important findings of the research are: 1-The concept of opposition is one of the important terminological topics in the science of the principles of jurisprudence (usul al-fiqh). 2-The concept of opposition has several types. 3- The validity of the concept of opposition is disputed, but it is generally accepted as evidence by the majority of scholars of the principles of jurisprudence (usul al-fiqh).